RETRACTED: Sustainable Energy Efficient Human-Centered Digital Solutions for ESG Megacities Development - Barykin, Sergey Evgenievich; Sergeev, Sergey Mikhailovich; Kapustina, Irina Vasilievna; Poza, Elena de la; Danilevich, Denis Vladimirovich; Mottaeva, Angela Bahauovna; Andreeva, Larisa Olegovna; Niyazbekova, Shakizada Uteulievna; Karmanova, Anna Evgenievna (Frontiers in Energy Research, 2022)
This study demonstrates algorithms that assist municipal administrations in making the best environmental decisions. They were created by large alpha-class municipal governments with assistance from the DEA and panel data analysis. Quarantine measures have significantly altered the structure and expansion of megacities during the last two years. The regulatory influence of such dispositive judgments is typically directed at economic companies with externalized activity. Relaxing epidemiological limits indicates a reduce safety of living circumstances, hence it is necessary to give choices for administrative decisions now. Tourists, cultural, scientific, and athletic event goers, students, educational institution attendees, and job seekers all migrate to these megacities. As a result, demand for municipal resources (common property resources) fluctuates throughout the year. The authors make use of mathematical and econometric modeling techniques as well as optimum solution theories. The criteria is functionality, which reflects a balance between maximum profit, comfort in living circumstances, the environment, and the need to avoid a market failure scenario. The ensuing results allow for the most optimal administrative decisions, such as the rate of environmental taxes. The empirical findings show that higher ESG performance and digital finance improve corporate financing efficiency, as well as the influence of ESG performance on energy efficiency, all at a 1% significance level.